Tantangan Etika Birokrasi di Era Revolusi 5.0 - Hikmah Muhaimin; Iqma Yuliasari; Nindy Lulu Nur Hidayah (Journal Law and Government, 2024)
The Indonesian bureaucracy plays an important role in the context of the industrial revolution 5.0. Maintaining bureaucratic ethics is as important for a bureaucrat as being flexible in dealing with technological advances. Thus, the researcher raises several problems, including how to prepare and share the origin of bureaucratic human resources so that they have ethical abilities and competencies in sync with the demands of the Industrial Revolution 5.0 and what are the ethical challenges that arise in the application of tasks and public services in the era of the Industrial Revolution 5.0. This research uses a qualitative methodology. Examining a program, event, activity, process, or group of people collectively is known as qualitative research. Literature study is the method used in this study to obtain data. By using this literature study method, researchers can gain a comprehensive understanding of the difficulties related to bureaucratic ethics in the context of the 5.0 Revolution. This study shares five primary obstacles that need to be overcome by bureaucracies to maintain their ethical compass in this day and age. First, the issue of privacy in facing the ocean of news. The discriminatory cracking procedure is the latter. Third, the "algocracy" accountability crisis. The digital divide in public services is fourth. Fifth, the decline of human values. The conclusion of this journal emphasizes how important it is to apply the concept of good governance to public services to improve governance standards. Conclusion The study notes that despite efforts to incorporate moral principles such as professionalism, responsibility, and integrity, institutional inflexibility, issue gaps, and dilemmas of nepotism and corruption continue to interfere with their implementation.